Differentially regulated gene expression in quiescence versus senescence and identification of ARID5A as a quiescence associated marker. Issue 5 (4th December 2017) - Anwar, Tarique; Sen, Bijoya; Aggarwal, Savera; Nath, Rhisita; Pathak, Niteen; Katoch, Ajay; Aiyaz, Mohamed; Trehanpati, Nirupma; Khosla, Sanjeev; Ramakrishna, Gayatri
Abstract : In multicellular organisms majority of the cells remain in a non‐dividing states of either quiescence (reversible) or senescence (irreversible). In the present study, gene expression signatures unique to quiescence and senescence were identified using microarray in osteosarcoma cell line, U2OS. It was noted that certain genes and pathways like NOD pathway was shared by both the growth arrest conditions. A major highlight of the present study was increased expression of number of chemokines and cytokines in both quiescence and senescence. While senescence‐associated secretory phenotype (SASP) is well known, the quiescence‐associated secretory phenotype (QASP) is relatively unknown and appeared novel in this study. ARID5A, a subunit of SWI/SNF complex was identified as a quiescence associated gene. The endogenous expression of ARID5A increased during serum starved condition of quiescence. Overexpression of ARID5A resulted in more number of cells in G0/G1 phase of cell cycle. Further ARID5A overexpressing cells when subjected to serum starvation showed a pronounced secretory phenotype. Overall, the present work has identified gene expression signatures which can distinguish quiescence from senescence. Abstract : The present work has identified gene expression signatures which can distinguish quiescence from senescence. Additionally the work has identified ARID5A as a quiescence associated gene.